The effect of the universal test and treat strategy on the kidney function in adults living with HIV in Zambia: A six-month multicenter cohort study - Lukundo Siame; Matenge Mutalange; Chitalu Chanda; Morgan Sakala; Chilala Cheelo; Kingsley Kamvuma; Geofrey Mupeta; Martin Chakulya; Memory Ngosa; Michelo Haluuma Miyoba; Situmbeko Liweleya; Sepiso K. Masenga; et al. (PLoS ONE, 2025)
Background Kidney disease is prevalent among people living with HIV (PLHIV), especially in Sub-Saharan Africa (SSA), due to complications of HIV infection, co-morbidities, and antiretroviral therapy (ART). Despite SSA shouldering a disproportionate burden of HIV, there is limited data on the effect of clinical and demographic factors on the kidney with the introduction of the Test and Treat policy. This study aimed to determine the incidence and factors associated with kidney impairment among PLHIV on ART in the Southern Province of Zambia. Methods We conducted a retrospective cohort study among 1216 adult individuals living with HIV who initiated ART between January 1, 2014, and July 31, 2016 [before test-and-treat cohort (BTT), n = 814] and August 1, 2016, and October 1, 2020 [after test-and-treat cohort (ATT), n = 402] without kidney function impairment at baseline, followed for 6 months in 12 districts of the Southern Province. The primary outcome was kidney function impairment, defined by an estimated glomerular filtration rate (eGFR) of < 60 ml/min/1.73m² estimated using the Modification of Diet in Renal Disease (MDRD) equation. We used multivariable logistic regression (xtlogit model) to identify factors associated with kidney function impairment. Statistical significance was set at p < 0.05. Results The median age was 36.4 years (interquartile range (IQR): 29.9, 43.3), and the majority of participants were women (57.2%, n = 695). Tenofovir Disoproxil Fumarate (TDF) and XTC exposure was noted among 1,173/1216 (96.5%) enrolled participants and 92.9% (26/28)of those with renal impairment. The overall cumulative incidence of kidney impairment was 2.3% (n = 28/1216: 95% confidence interval (CI) 3%, 5%), and it was higher BTT compared to the ATT (2.8% vs. 1.2%). Every unit increase in age was associated with an increased odds of having kidney function impairment (adjusted odds ratio (AOR):1.05, 95% CI: 1.01–1.09, p = 0.008).. Participants from urban facilities also had a higher risk (AOR: 5.14, 95% CI: 1.95–13.55, p < 0.001). In contrast, being enrolled after the implementation of the “test-and-treat” policy was associated with lower odds of having kidney function impairment (AOR: 0.45, 95% CI: 0.12–0.97, p = 0.042). Conclusions This study found a 2.3% incidence of kidney function impairment among PLHIV within 6 months of initiating ART. An increase in age and receiving care at an urban facility were positively associated with kidney function impairment, whereas ART enrollment following the implementation of the “test-and-treat” policy was negatively associated. This study highlights the benefits of early ART initiation on kidney function, reinforcing the need to maintain the universal test-and-treat policy.